Digital technologies in the system of teaching students at the university - E. Z. Imaeva; N. A. Sukhareva; Yu. V. Kostikova (Вестник университета)
The study aims at identifying the role of the digital technologies in the system of teaching students at the university. The following methods were used in the study: testing, questioning, analysis of performance results, mathematical methods of data processing, etc. Methods for diagnosing learning motivation and emotional attitude to learning, studying the levels of formation of students’ cognitive interests (author’s method), a questionnaire for assessing students’ knowledge in the field of research activities were applied as well. The data of the students’ final progress in subjects were also analysed. An analysis of the main results of the study allows us to conclude: students who were asked to use digital technologies in teaching showed significant differences before and after the experiment on all scales of the study (the learning motivation level, the cognitive interest level, the knowledge level in the research activities field, assessment of the final performance in subjects). The analysis of the results also showed that according to all the data obtained at the stage of the control experiment, the reliability of the differences in the conclusions of the experimental and control groups on all scales of the study is confirmed.